Cancer And Rorschach From An Existential Perspective (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This research aims to detect indicators in the responses to Rorschach tests administered on female patients diagnosed with cancer who are aware of their disease. The framework of this theory is existential phenomenology as it aids comprehending the experiences of the examinées as expressed in their responses, which, in turn, may help to develop therapeutic strategies.
Keywords: Cancer; existence; Rorschach indicators; corporeality